Performance of Paraloid B72® combined with the application of biocides on wood degraded by fungi - Henriques, J. D. (2010)
When timber elements in heritage buildings are moderately degraded by fungi and assuming underlying moisture problems are solved, two actions can be taken: i) use a biocide product to stop fungi activity ii) consolidate the degraded elements so that the timber keeps on fulfilling its structural and decorative functions. Indeed, the option of maintaining in the building the original (even though deteriorated) timber has been gaining more and more importance, as the loss any element may contribute to the loss of the historical identity of the building. This paper presents the laboratory work performed with the purpose of understanding the mechanical performance of maritime pine timber degraded by fungi (with mass losses lower than 20%) when subjected to consolidation by impregnation with Paraloid B72®, combined with the previous application of a biocide. Three commercially available pre-selected biocide products were used: a light organic solvent (X), a boron water-based (BC) and a water-based emulsion (A). After the products were applied to five sets of specimens (Control, PB72, X+PB72, BC+PB72, A+PB72) these were subjected to mechanical tests: axial compression test (NP618) and resistance to indentation (ISO 3350). Four similar sets of replicates were subjected to an evaporation ageing procedure (EN73) after the products were applied and equally tested. An increase in mechanical strength was observed for the consolidation product with no significant influence of the previous use of biocide product. The specimens subjected to ageing showed a slightly better general mechanical performance than those not aged.